Young infants' exposure to organophosphate esters: Breast milk as a potential source of exposure. (October 2020) - Hammel, Stephanie C.; Zhang, Sharon; Lorenzo, Amelia M.; Eichner, Brian; Stapleton, Heather M.; Hoffman, Kate
Graphical abstract: Highlights: Biomarkers of organophosphate ester exposure were detected frequently among infants. TCIPP metabolite levels were significantly higher at 6 weeks than at 12 months of age. Infants who were currently receiving breast milk had higher levels of TCIPP metabolites. Breastfeeding and owning more children's products were associated with higher BDCIPP. Abstract: Organophosphate esters (OPEs) are applied as both flame retardants and plasticizers to a variety of consumer items such as home furnishings, construction materials, and children's products. While some assessments have characterized exposure among toddlers and young children, little is known about the OPE exposure among infants, who are a vulnerable population due to their rapid development. Here, we collected spot urine samples from 6-week-old (n = 100) and 12-month-old infants (n = 63), with about half of the infants evaluated at both ages (n = 52), to characterize OPE exposure and determine what factors contributed to higher exposures. Five of six OPE metabolites analyzed were detected frequently (>70%). Diphenyl phosphate was detected in every urine sample, while bis(2-chloro-isopropyl) phosphate (BCIPP) was the most abundant metabolite measured overall. Concentrations of bis(1-chloro-2-propyl) 1-hydroxy-2-propyl phosphate (BCIPHIPP) and BCIPP [i.e., metabolites of tris(2-chloro-isopropyl) phosphate (TCIPP)] were significantly greater among 6-week-old infants compared to 12-month-olds, while levels of other OPE metabolites were not statistically different in the first year of life. OPE metabolites were generally correlated with one another in samples collected at each age (rs  = 0.25–0.75; p < 0.05), and except BCIPHIPP, concentrations of the same metabolite were correlated over time (rs  = 0.41–0.53; p < 0.05). Breastfeeding at 6 weeks of age and owning a larger number of children's products were associated with increased concentrations of urinary BDCIPP. Infants who were currently receiving breast milk had higher levels of TCIPP metabolites; urinary BCIPP concentrations were 6.2 times higher in infants receiving breast milk at 6 weeks of age, and BCIPHIPP levels were 2.2 times higher for 12-month-old infants receiving breast milk (10 β  = 7.2; 95% CI: 1.6–32.1 and 10 β  = 3.2; 95% CI: 1.2–8.1, respectively). Differences in the predominant TCIPP metabolite associated with breastfeeding may suggest differences in metabolism with age. Cumulatively, our results suggest levels of OPE exposure may be higher for infants than other age groups, including toddlers and older children.